Nonconceptual Content, Causal Theory, and Realism - Błażej Skrzypulec (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
In this paper the connections between the nonconceptual content of perceptual states and realism are considered. In particular, I investigate the argument for realism that uses the notion of nonconceptual content, specifically the version proposed by Raftopoulos in Cognition and Perception. To evaluate the argument two forms of realism are identified: (1) correlation realism (CR), according to which distinctions in perceptual content correlate with distinctions in the environment, and (2) ontological realism (OR), according to which perceptual content and perceived reality are both organized according to the same set of ontological categories. First, it is argued that the distinction between nonconceptual and conceptual content is irrelevant for the justification of CR. In particular, the notion of nonconceptual content is neither sufficient nor is it necessary for such justification. Second, it is stated that the version of the causal theory of perception that is used in the argument considered already assumes ontological realism. What is more, the weaker version of the causal theory, that does not presuppose OR, is too weak to justify ontological realism in combination with assumptions about nonconceptual content and the successfulness of perception.
Keywords: philosophy of perception; realism; nonconceptual content; conceptual content